Nitric-oxide-driven oxygen release in anoxic Pseudomonas aeruginosa - Mads Lichtenberg (Elsevier, 2021)
Summary: Denitrification supports anoxic growth of Pseudomonas aeruginosa in infections. Moreover, denitrification may provide oxygen (O2) resulting from dismutation of the denitrification intermediate nitric oxide (NO) as seen in Methylomirabilis oxyfera. To examine the prevalence of NO dismutation we studied O2 release by P. aeruginosa in airtight vials. P. aeruginosa rapidly depleted O2 but NO supplementation generated peaks of O2 at the onset of anoxia, and we demonstrate a direct role of NO in the O2 release. However, we were not able to detect genetic evidence for putative NO dismutases.The supply of endogenous O2 at the onset of anoxia could play an adaptive role when P. aeruginosa enters anaerobiosis. Furthermore, O2 generation by NO dismutation may be more widespread than indicated by the reports on the distribution of homologues genes. In general, NO dismutation may allow removal of nitrate by denitrification without release of the very potent greenhouse gas, nitrous oxide.